Legal Protection for Indigenous Peoples for the Masela Block Gas Infrastructure - Laturette, Adonia Ivonne; Sainyakit, Sri Ayu Junita (SASI, 2023)
Introduction: Customary law communities can own land rights, including the customary law community of Latdalam Village who have rights over land called land owned by relatives/soa whose control rights are carried out jointly.Purposes of the Research: This writing aims to determine the existence of the customary law community over Soa Olusi's land and the legal protection of the customary law community of Latdalam Village over Soa Olusi's land rights in the framework of the development of the Masela Block liquefied natural gas infrastructure.Methods of the Research: This research is a normative research that refers to the legislation and legal materials related to the substance of the research, then linked to the main problems in this research. The approach taken in this research is a statutory approach and a conceptual approach.Results of the Research: Based on the results of the study, the land rights of the Soa Olusi customary law community in Latdalam Village are considered to still exist and are recognized in accordance with Act number 5 year 1999 article 2. And the process of transferring land rights belonging to Soa Olusi through buying and selling has an invalid legal status / legal defect because it does not comply with applicable procedures according to applicable customary law and Indonesian law. In relation to development for the public interest, the government must provide compensation and recognition of those who have land rights, namely Soa Olusi, and if the government is wrong or wrong in providing compensation and recognition, then there is legal protection for the Soa Olusi community, namely preventive legal protection. and repressive legal protection.